Effect of osmotic dehydration on the quality of dried mangoes (Magifera indica L. var. Katchamita). - Ledda, Wendy Eyan (2015.)
The study determined the effect of osmotic dehydration on the quality of dried mangoes (Mangifera indica L.) of Katchamita cultivar. Mango slices were subjected to sugar solutions of 40% w/v, 50% w/v and 60% w/v. The pretreated mango slices were dehydrated using a cabinet dryer at 65 ± 5°C for 6 hours. The dried slices were then assessed of the physicochemical properties like water activity, moisture content, tiratable acidity and total sugars & microbiological properties through Total Plate Count & Yeast & Mold Count within a 14-day storage period. Sensorial qualities were also evaluated using Preference Rank Test and Descriptive Analysis. Color, texture, sweetness and sourness were also assessed. Results showed that osmotic dehydration along with cabinet-drying has significantly reduced the water activity (0.632-0.644) and moisture content (15-03-15.99%) but increased the titratable acidity (0.430-0.511%) and total sugar content (30.3-31.5%) of the mango slices. Microbial assessment showed that microbial load has reduced and are within acceptable limits during the set storage period. Sensory Evaluation revealed that dried Katchamita mangoes osmotically dehydrated in 40% w/v sugar solution were the most preferred. Increased sugar concentration resulted to darker color, more tender texture, increased sweetness and reduced sourness in the dried mangoes. The results suggest that osmotic dehydration done prior to drying of Katchamita mangoes can result to a dried product with an overall quality that conforms to standards.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Mango; Mangifera indica L; Dehydration of mango; Osmotic dehydration